Burden of Care Implications and Association of Intracranial Hypertension With Extremely Severe Post-traumatic Amnesia After Traumatic Brain Injury: A 5-Year Retrospective Longitudinal Study - Quach, Nhung T.; Ehsanian, Reza; Dirlikov, Benjamin; Sechrist, Samantha; Mohole, Jyodi; McKenna, Stephen; Isaac, Linda; Duong, Thao T. (Frontiers in Neurology, 2019)
Post-traumatic amnesia (PTA) is characterized by a state of disorientation and confusion following traumatic brain injury (TBI). Few studies have looked at the effect of prolonged PTA on the functional outcomes beyond one year post-injury. This study aims to evaluate the burden of care in individuals with extremely severe PTA (esPTA; PTA > 28 days) from acute inpatient rehabilitation admission to five years post-injury as well as the association between intracranial hypertension (ICH; Intracranial pressure (ICP) > 20mmHg) and esPTA status. Three hundred and forty-two individuals with moderate to severe TBI enrolled in the Northern California TBI Model System (TBIMS) of Care were included in this study. The FIM® instrument was chosen as the outcome measurement as it is a widely used functional assessment in the rehabilitation community. Repeated measure ANOVA revealed greater burden of care based on FIM® total scores (p < .001) from admission to five-year follow-up for the esPTA group compared to the non-esPTA group (PTA < 28 days). Unlike the non-esPTA group where FIM® total score plateaued one year post-injury, FIM® total score continued to improve up to two years post-injury for the esPTA group. The odds of developing esPTA was approximately three times higher for individuals with ICH versus individuals without ICH (p < .001). In conclusion, individuals with esPTA have increased short- and long-term burden of care and the presence of ICH during hospitalization increased the odds of experiencing esPTA. These results may help the rehabilitation team and family in planning care post rehabilitation discharge.